Peran Program Kampus Mengajar dalam Penguatan Keterampilan Sosial (Social Skills) Mahasiswa (Studi Deskriptif Program MBKM (Merdeka Belajar Kampus Merdeka) di FKIP Universitas Sultan Ageng Tirtayasa) : Penelitian - Anisa Tulhalizah; Wika Hardika Legiani; Ria Yuni Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Abstract English version, written using Time New Roman-10, italic. Abstract contains research aim/purpose, method, and reseach results; written in one paragraph, single space among rows, using past tense sentences. This study aims to describe the role of the Kampus Mengajar program in strengthening the social skills of students participating in the Merdeka Belajar Kampus Merdeka (MBKM) program at FKIP, Sultan Ageng Tirtayasa University. The research employed a qualitative descriptive method using observation, interviews, and documentation. The focus included cooperation, assertive behavior, responsibility, empathy, and self-control. The findings show that students’ social skills were strengthened through collaborative activities, constructive communication, and adaptation to the school environment. Programs supporting this strengthening included teaching assistance, numeracy and literacy programs, and technology adaptation. Key supporting factors were collaboration with teachers, school support, and student enthusiasm. The study also identified inhibiting factors, but they did not have a significant impact on the strengthening process. Thus, the Kampus Mengajar program plays an important role in strengthening students’ social skills as personal and professional preparation in education.